2019
DOI: 10.3390/ma12193269
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Structural Characteristics of Titanium Alloy Products Manufactured Using Additive Technologies by Combining the Selective Laser Melting and Direct Metal Deposition Methods

Abstract: Titanium alloy product manufacturing is traditionally considered to be a rather difficult task. Additive manufacturing technologies, which have recently become quite widespread, can ensure the manufacture of titanium alloys products of an arbitrary geometrical shape. During this study, we have developed a methodology for manufacturing titanium alloys products using additive technologies on FL-Clad-R-4 complex of laser melting of metals by combined Selective Laser Melting (SLM) and Direct Metal Deposition (DMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The study of the microstructure of the obtained samples showed that a mechanical mixture of α-and β-phases is formed as a result of melting (Figures 7 and 8). Earlier, we carried out work [26] in which we studied, in more detail, the phase composition of the samples obtained from the powder Ti-6Al-4V using similar fusion modes. The presence of two phases (α and β) in the structure is confirmed by XRD results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of the microstructure of the obtained samples showed that a mechanical mixture of α-and β-phases is formed as a result of melting (Figures 7 and 8). Earlier, we carried out work [26] in which we studied, in more detail, the phase composition of the samples obtained from the powder Ti-6Al-4V using similar fusion modes. The presence of two phases (α and β) in the structure is confirmed by XRD results.…”
Section: Resultsmentioning
confidence: 99%
“…The porosity does not exceed 1% with direct laser melting, but the movement of the laser along different trajectories, with the possibility of texture formation in different metallographic planes [25][26][27], leads to the appearance of properties anisotropy [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations